Endometriosis in patients with irritable bowel syndrome: Specific symptomatic and demographic profile, and response to the low FODMAP diet. (17th March 2017) - Moore, Judith S.; Gibson, Peter R.; Perry, Richard E.; Burgell, Rebecca E.
Abstract : Background: Women with endometriosis are frequently misdiagnosed with irritable bowel syndrome (IBS) for some time before a correct diagnosis is made. Visceral hypersensitivity is a key feature in both conditions. Aims: To determine if there are distinct symptom patterns in women with IBS and endometriosis, and to determine the response of these women to a low FODMAP diet in comparison to those with IBS alone. Materials and methods: A retrospective analysis of prospectively collected data from women attending a specialist IBS service in Christchurch New Zealand. Data from those who met Rome III criteria for IBS were sorted into two groups: concurrent endometriosis and those with IBS alone. Demographics and symptom patterns were identified from a prospective questionnaire. A low FODMAP (fermentable oligosaccharides, disaccharides, monosaccharides and polyols) diet was taught to all women as the primary therapeutic intervention. Responses to the diet were noted against their ultimate disposition. Results: Of the 160 women who met Rome III criteria for IBS, 36% had concurrent endometriosis. The presence of dyspareunia ( P  > 0.0001), referred pain ( P  = 0.005), bowel symptoms exacerbated by menstruation ( P  = 0.0004) and a family history of endometriosis ( P  = 0.0003) were associated with concurrent endometriosis. Seventy two percent of these women reported a >50% improvement in bowel symptoms after four weeks of a low FODMAP diet compared with 49% in those with no known endometriosis ( P  = 0.001, odds ratio 3.11, 95% CI, 1.5–6.2). Conclusions: Women with concurrent endometriosis and IBS report a unique symptom phenotype. The low FODMAP diet appears effective in women with gut symptoms and endometriosis.